Network Stack as a Service in the Cloud - Niu, Zhixiong; Xu, Hong; Han, Dongsu; Cheng, Peng; Xiong, Yongqiang; Chen, Guo; Winstein, Keith (HotNets-XVI, 2017)
The tenant network stack is implemented inside the virtual machines in today’s public cloud. This legacy architecture presents a barrier to protocol stack innovation due to the tight coupling between the network stack and the guest OS. In particular, it causes many deployment troubles to tenants and management and efficiency problems to the cloud provider. To address these issues, we articulate a vision of providing the network stack as a service. The central idea is to decouple the network stack from the guest OS, and offer it as an independent entity implemented by the cloud provider. This re-architecting allows tenants to readily deploy any stack independent of its kernel, and the provider to offer meaningful SLAs to tenants by gaining control over the network stack. We sketch an initial design called NetKernel to accomplish this vision. Our preliminary testbed evaluation with a prototype shows the feasibility and benefits of our idea.